Learning Behavior Effectiveness Management of Equivalent Education - Joko Sutarto (Jurnal Aplikasi Manajemen, 2011)
The effectiveness the learning process of Package B Equivalence Education is not only influenced by inner factors of tutors knowledge and motivation, but also influenced by the out work climate. This study aims to analyze the influence of knowledge factors, the motivation, and work climate, to the effectiveness of the learning process of Package B Equivalence Education. This study is ex post-facto as well as descriptiveevaluative- correlative in nature. Sample to be studies were the 122 active Semarang recidental-based SKB-Centers tutors of Package B Equivalence Education. Following a cluster proportional random sampling technique. A set of rating-scale questionaries was used during to collect the data. Data were then analysed using a descriptive-analysis model and regression analysis. This study found that: (a) knowledge factors with contributed a direct, dominant influence to the effectiveness learning process with a percentage 12,25%; (b) motivation factors with contributed a direct influence to the effectiveness learning process with a percentage 18,49%; and (c) work climate factor with contributed a direct influence to effectiveness learning process with a percentage 44,89%. This study imply that to improve the quality of both the effentiveness learning process of Package C Program, the following needs should be met establishment of tutors knowledge factors, motivation factors, and work climate factors. Based on the above findings this study recommends that in order to improve the performance of SKB-Centres the following needs should be met; (a) SKB-centres to improve the centres’ work climate; (b) policymakers, both at national and regional level, to confirm the availability of funding to finance the Package B Equibalence Education Program; (c) policymakers to take into mind seriously the issue of learning facilities availability.Keywords: Management, Effectively, Knowledge, Motivation, and Work Climate-Factors.